2020
DOI: 10.1111/jvs.12910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of white‐tailed deer exclusion on the plant community composition of an upland tallgrass prairie ecosystem

Abstract: Questions: Grasslands support ecosystem services, promote diversity, and assist in carbon sequestration. However, grasslands worldwide are diminishing in area, and understanding the drivers shaping the remaining grasslands is critical for their maintenance. The North American tallgrass prairie covers approximately 13% of its historical range and is shaped by fire and herbivory. Fire frequency negatively correlates with plant species richness, while bison (Bos bison)-the historical grazers-offset this effect. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
(77 reference statements)
2
1
0
Order By: Relevance
“…Deer florivory might cause grassland communities to lose poorly defended forbs, whereas grazers such as B. bison consuming grasses might increase forb abundance. For example, our study reinforces a similar finding from the Konza Prairie that white-tailed deer have no detectable effect on dominant C4 grasses (Bloodworth et al 2020 ). However, by explicitly looking at different forb species, we found that they could have markedly different responses to deer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Deer florivory might cause grassland communities to lose poorly defended forbs, whereas grazers such as B. bison consuming grasses might increase forb abundance. For example, our study reinforces a similar finding from the Konza Prairie that white-tailed deer have no detectable effect on dominant C4 grasses (Bloodworth et al 2020 ). However, by explicitly looking at different forb species, we found that they could have markedly different responses to deer.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to forbs, we found greater abundance of the C3 grass species P. oligosanthes in unfenced plots and no effect of fencing on the abundance of the native C4 grass S. nutans , consistent with deer being browsers with minimal impact on grasses with intercalary meristems and low-nutrient tissues (Gordon and Herbert 2019 ; Bloodworth et al 2020 ). We speculate that the greater biomass of P. oligosanthes outside the fence may be a response to deer trampling and/or increased light availability.…”
Section: Discussionsupporting
confidence: 59%
“…While our 15% reduction in richness and 12% in plant diversity were about half the effect size found by Richardson & Stilling, we suspect that future studies will reveal that the effects of tortoise exclusion will increase with time. Significant impacts of herbivore exclusion experiments after one year of exclusion are rare in the literature, and significant effects build up after multiple years (Moorhead et al 2017, Shelton et al 2014, Frank, Rathfon and Saunders, 2018Schäfer et al, 2019;Bloodworth, Ritchie and Komatsu, 2020). In longleaf pine forests in southern Alabama, white-tailed deer exclusion had no effect on plant diversity and cover after four years of exclusion (Brockway and Lewis, 2003).…”
Section: Discussionmentioning
confidence: 99%